The Effect of the Supplementary Feeding Program on Changes in the Body Weight of Undernourished Infants Aged 6-11 Months at the Tiley Health Center - Nabita Ode Mansa; Anik Purwati (International Journal of Medicine and Health, 2025)
Toddlers are a vulnerable group prone to health problems and malnutrition due to their rapid growth and high nutritional needs. Nutritional status serves as an indicator of adequate dietary intake, commonly assessed through weight and height measurements. Malnutrition, particularly among children aged 2-5 years, often occurs as they transition to family diets while maintaining high physical activity levels. Appropriate complementary feeding starting at six months (MP-ASI) is essential to support optimal growth and development. The Complementary Feeding Program includes porridge for infants aged 6-11 months and biscuits for children aged 12-24 months, aiming to improve nutritional status, especially among low-income families. Supplementary feeding (PMT) is an intervention designed to enhance the nutritional status of malnourished children without replacing their main daily meals. This study aims to examine the effect of the supplementary feeding program on weight changes among malnourished infants aged 6-11 months at the Tiley Health Center. A pre-experimental one-group pretest-posttest design was used with total sampling of 20 mothers with malnourished infants. Data were collected using questionnaires and weight observation sheets and analyzed using a paired t-test. The results showed a significant effect (p < 0.05), indicating that the supplementary feeding program improves infants’ weight.